A sequence { a i } is defined by the recurrence relation a n = 4 0 − 4 a n − 1 with a 0 = − 4 . There exists real valued constants r , s and t such that a i = r ⋅ s i + t for all non-negative integers i . Determine r 2 + s 2 + t 2 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
When i = 0 , r + t = − 4 . ---(1)
When i = 1 , r ⋅ s + t = 4 0 − 4 ⋅ ( − 4 ) = 5 6 . ---(2)
When i = 2 , r ⋅ s 2 + t = 4 0 − 4 ⋅ 5 6 = − 1 8 4 . ---(3)
(2)–(1) r ⋅ ( s − 1 ) = 6 0 .
(3)–(2) r ⋅ s ⋅ ( s − 1 ) = − 2 4 0 .
If we divide the 2 equations, we get s = − 4 . Then r = − 5 6 0 = − 1 2 . Substituting r into (1), we get t = 8 .
So r 2 + s 2 + t 2 = ( − 1 2 ) 2 + ( − 4 ) 2 + 8 2 = 2 2 4
One has r x s^2 + t = - 184, r x s + t = 56, r + t = - 4. Clearly, -t = r + 4. One has s = (56 - t) / r = 60 / r + 1. One has s^2 = (-184 - t) / r = - 180 / r + 1. Now, s^2 + 3 s = - 180/r + 1 + 180/r + 3, therefore s^2 + 3 x s = 4, and s 1 = 1, s 2 = -4. But s<>1, because - 184 = r + t <> 56 = r + t. Then s = - 4. One obtain -4 x r + t = 56, r + t = - 4, so 5 x r = -60, and r = - 12 and t = 8. Consequently, r^2 + s^2 + t^2 = (-12)^2 + (-4)^2 + 8^2 = 144 + 16 + 64 = 144 + 80 = 224.
by using the recurrence relation we obtain a 1 = rs + t = 56, a 2 = rs^2 + t = -184, a_3 = rs^3 + t = 776. Simply by rearranging those equations we can get s = \frac {776 - t}{-184-t} = \frac{-184-t}{56-t}. Solving this we get t=8 and by plugging back t=8 we get s=-4. Lastly, 56 = r \cdot (-2) + 8, giving us r = -12. So r^2 +s^2 +t^2 = 144 + 16 + 64 = 224.
I started by listing out the first few terms of a: -4, 56, -184 Next I equated them in terms of r, s and t: r + t = -4 rs + t = 56 rs^2 + t = -184 Then, I subtracted adjacent terms and got: rs - r = 60 rs^2 - rs = s(rs - r) = s(60) = -240 By factoring s out of the second equation and plugging in 60 for rs - r we can get s = -4. Finally we can solve for r and t by plugging in s back in to find r and then r back in to find t. And we get r = -12 and t = 8.
a
0
= -4
a
1
= 56
a
2
= -184
r + t = -4
rs + t = 56
r
s
2
+ t = -184
By solving these equations,
we get s = -4 r = -12 t = 8
r 2 + s 2 + t 2 = ( − 4 ) 2 + ( − 1 2 ) 2 + 8 2
r 2 + s 2 + t 2 = 224
As an = 40- 4an-1 and ai = r • si + t, a0 = -4 = r + t; ----------- 1 a1 = 56 = rs + t -----------2 a2 = -184 = rs2 + t ----------3 2–1: rs – r = r(s-1) = 60 ----------4 3-1: rs2 – r = -180 ----------5 3-2: rs2 – rs = rs(s-1) = -240 ----------6 6-4: (s-1)(rs-r) = -300 ----------7 7÷4: s-1 = -5 s=-4 4: r(s-1) = 60 -5r = 60 r = -12 1: r + t = -4 t= 8 Therefore, r2 + s2 + t2 = 144 + 16 + 64 = 224
a(0) = -4 = r+t a(1) = 40-4(-4) = 56 = rs+t a(2) = 40--(-56) = -184 = rs^2 +t
From a(0) and a(1) we can get 60 = r(s-1)
From a(0) and a(2) we can get -180 = r(s-1)(s+1)
From these two equations we can get r = -12 , s = -4 , t = 8
r^2 + s^2 + t^2 = 224
put i=0,1,2 for n in an=40−4an−1 ai=r⋅si+t then we get r+t=-4 rs+t=56 rs.s+t=-184 solving the above eq we get r=-12,s=-4,t=8 put in the result we get r2+s2+t2=224
eq1: r+t=-4 eq2: rs+t=56 eq3: r(s^2)+t=-184
eq2 - eq1: r(s-1)=60 eq3 - eq2: rs(s-1)=-240 therefore, s=-4 it follows that r=-12 and t=8
r^2+s^2+t^2=(-12)^2+(-4)^2+8^2=224
Solution 1: Set b n = a n − 8 . Then, b 0 = − 1 2 . We also have that b n = 4 0 − 4 a n − 1 − 8 = 3 2 − 4 a n − 1 = − 4 ( a n − 1 − 8 ) = − 4 b n − 1 . Substituting recursively, we have, b n = ( − 4 ) × b n − 1 = ( − 4 ) 2 × b n − 2 = ( − 4 ) n × b 0 = ( − 1 2 ) ( − 4 ) n . Thus, a n = b n + 8 = ( − 1 2 ) ( − 4 ) n + 8 , for all non-negative n , with r = − 1 2 , s = − 4 and t = 8 . Therefore, r 2 + s 2 + t 2 = 1 4 4 + 1 6 + 6 4 = 2 2 4 .
Solution 2: Substitute the condition a i = r ⋅ s i + t into a n = 4 0 − 4 a n − 1 . We get, r ⋅ s n + t = 4 0 − 4 r ⋅ s n − 1 − 4 t . Rearranging, we have, ( r s + 4 r ) ⋅ s n − 1 = 4 0 − 5 t . Since the RHS is constant over all n , the LHS must be constant over all n . If s n − 1 is a constant (i.e. s = 0 or 1 ), then a i will be a constant sequence, which is a contradiction. Hence, s n − 1 is not a constant, so the coefficient ( r s + 4 r ) must be the constant 0. Likewise, if r = 0 , then a i will be a constant sequence, hence r = 0 and s + 4 = 0 ⇒ s = − 4 . This gives us that 4 0 − 5 t = 0 ⇒ t = 8 . Now, subsituting in the value at i = 0 , we get − 4 = r ( − 4 ) 0 + 8 ⇒ r = − 1 2 . Hence, a i = ( − 1 2 ) ( − 4 ) i + 8 , and r 2 + s 2 + t 2 = 2 2 4 .
Three unknowns, therefore, generate three equations to solve.
Solve them any way you like.
Problem Loading...
Note Loading...
Set Loading...
a n = 4 0 − 4 a n − 1 a n − 8 = − 4 ( a n − 1 − 8 ) . Let b n = a n − 8 for all natural numbers n . Then, the original equation becomes b n = − 4 ( b n − 1 ) , from which we conclude that b n = ( − 4 ) n b 0 . Since b 0 = a 0 − 8 = − 4 − 8 = − 1 2 , thus b n = a n − 8 = ( − 1 2 ) ( − 4 ) n . Therefore a i = ( − 1 2 ) ( − 4 ) i + 8 . We thus calculate that r 2 + s 2 + t 2 = ( − 1 2 ) 2 + ( − 4 ) 2 + ( 8 ) 2 = 2 2 4 .
[Latex Edits, edits for clarity - Calvin]